Relationship between Age, Gender and Low Back Pain in Patients Referred for Magnetic Resonance Imaging of Lumbosacral Spine at Ahmadu Bello University Teaching Hospital, Zaria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Low back pain (LBP) is a symptom of many lumbosacral spine abnormalities which are prevalent in all occupational groups in our environment. Its frequency and severity are significantly related to age and gender.Aims:To determine the relationship between age, gender and LBP in patients referred for magnetic resonance imaging (MRI) of lumbosacral spine.Settings and Design:A cross sectional study at Ahmadu Bello University Teaching Hospital, Zaria.Materials and Methods:The study was conducted within 4 years at the MRI suite of the Department of Radiology, on 200 patients who had LBP who had MRI scan.Statistical analysis used:Data from the questionnaires were sorted and entered into Microsoft Excel. Analysis was performed using the Statistical Package for Social Sciences Version 22.0.Results:There is male preponderance, with a male to female ratio of 1.6:1. The ages ranged from 11 to 80 years, with a mean of 47.8 + 1.4, and the peak incidence (55 [27.5%]) is in the fourth and fifth decades of life. A statistically significant association (χ2 = 33.9; P < 0.001) was also found between the severity of LBP and ageing. Majority of the patients (172 [86%]) had intervertebral disc prolapse/herniation, out of which 104 (60.5%) were males and 68 (39.5%) were females.Conclusion:Patients with lumbar disc prolapse had early age incidence with male preponderance. The incidence of lower level disc involvement was more, and there was no significant decadal difference in presentation, when both protruded and extruded types of disc prolapse were compared to age and gender.